Investigation of body awareness, perceived stress level, postural awareness and habits and musculoskeletal pain in people living with overweight and obesity: A comparative study - Dengiz, Aziz; Altin, Fatma Nur (Pergamon-Elsevier Science Ltd, 2025)
Background: Obesity is a major global health concern associated with physical and psychological risks. These factors may influence body awareness, stress, posture, and pain. This study aimed to examine body awareness, perceived stress level, postural awareness and habits, and musculoskeletal pain in people living with obesity (PLWO). Methods: This study was conducted with 397 participants aged 18-65 years, categorized into normal-weight (mean: 21.44 +/- 4.78 (N:130 ( %32.7)) overweight (mean: 27.44 +/- 1.37 (N:118 ( %29.72 and PLWO (mean: 33.99 +/- 3.47 (N:149 ( %37.53)) groups. Data were collected online using structured questionnaires. Body awareness was assessed with the Body Awareness Questionnaire, postural awareness with the Postural Habits and Awareness Scale, and stress levels with the Perceived Stress Questionnaire. Anxiety and depression were measured using the Hospital Anxiety and Depression Scale, while pain and sleep quality were evaluated with Visual Analogue Scale. Group differences were analyzed using One-Way ANOVA. Hochberg's GT2 or Games-Howell tests were used for post hoc comparisons based on variance homogeneity. Statistical significance was set at p < 0.05. Results: Significant differences were found in body awareness scores among groups (F = 4.544, p = 0.011), with healthy-weight people scoring higher (87.05 +/- 17.22) than overweight (81.65 +/- 18.48) and PLWO (81.42 +/- 15.96). Perceived stress levels were significantly elevated in overweight (41.55 +/- 8.97) and PLWO group (44.44 +/- 7.65) compared to healthy-weight people (26.66 +/- 6.00) (p < 0.001). Musculoskeletal pain and sleep disturbances were also significantly more frequent in overweight and PLWO. Healthy-weight people demonstrated greater postural (11.70 +/- 1.71) and positional awareness (38.7 +/- 5.0), while PLWO scored higher in postural habits (15.77 +/- 3.07). Conclusion: People living with obesity showed impaired body and positional awareness alongside increased stress and maladaptive postural habits, which may contribute to functional limitations. Targeted interventions enhancing body awareness and stress management are therefore essential to address these deficits.
Keywords: Obesity; Body image; Posture; Psychological stress